Assessment of Fish Fauna In Oguta Lake, Imo State, Niger Delta, Eastern Nigeria - K, Osijaye Gabriel; G, Bob-Manuel Faye-Ofori; F, Igbani (Darul Yasin Al Sys, 2024)
A fifty-seven (57) week investigation was carried out from September, 2019 to September, 2020 covering wet and dry seasons, to determine the fish fauna and its nomenclature in the Oguta Lake, Imo state, Niger Delta, eastern Nigeria. This research work was aimed at providing information on the fish stock and fish identification. During the assessment, fish samples were randomly collected from fishers twice weekly from five sampling stations along the River. The fishes collected were counted, and identified with identification keys. Species diversity and catches were analyzed using analysis of variance (ANOVA P<0.05) and Pearson correlation (2 tailed). The diversity and relative abundance were determined using standard methods. Results revealed that, the River was composed of 43 fish species belonging to 18 families, 10 orders and 29 genera from a total catch of 4,250. Fish species diversity was reported highest in the family Cichlidae (18.60%), Characidae (13.95%), Mormyridae and Bagridae (9.30%), Mochokidae (6.98%), Citharinidae; Clariidae; Schilbeidae; Polypteridae and Channidae (4.65%), Cyprinidae; Distichodontidae; Notopteridae; Hepsetidae; Malapteruridae; Osteoglossidae; Protopteridae and Gymnarchidae (2.33%). Fishing gears used were cast nets , gill nets, gura net traps, seine nets, drag nets, dugout canoe, drift nets, longlines, hooks and lines, baskets; spears. This river showed high fish species diversity, although some species showed higher diversity values than others due to fish gear types, mesh size, duration and station. There was a very high correlation of fish species in station 2, 3 and 4; there was no correlation of species in station 5 with stations 4, 3, 2 and 1. This study could serve as a baseline data to relevant bodies in the management and sustainability of the fisheries resources. The human activities along the Oguta Lake should be checked to avoid undue alteration of the ecosystem and subsequently the fishing grounds and fish species habitats. The fish species of this lake is said to be endangered of its fish species abundance and distribution.